2006
DOI: 10.1109/tit.2006.876256
|View full text |Cite
|
Sign up to set email alerts
|

Optimal deployment of large wireless sensor networks

Abstract: Abstract-A spatially distributed set of sources is creating data that must be delivered to a spatially distributed set of sinks. A network of wireless nodes is responsible for sensing the data at the sources, transporting them over a wireless channel, and delivering them to the sinks. The problem is to find the optimal placement of nodes, so that a minimum number of them is needed.The critical assumption is made that the network is massively dense, i.e., there are so many sources, sinks, and wireless nodes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 17 publications
0
55
0
5
Order By: Relevance
“…The p = 2 case can be viewed as a trade-off between packet delay and optimal load balancing. Furthermore, in [4] it is proved that while maintaining connectivity of network, minimizing (5) minimizes the number of nodes required to be deployed after the optimizer is discretized. Also, it is shown in [2] that the vector field that minimizes (5), D * (z), has the following property:…”
Section: Background: Continuous Information Flow Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The p = 2 case can be viewed as a trade-off between packet delay and optimal load balancing. Furthermore, in [4] it is proved that while maintaining connectivity of network, minimizing (5) minimizes the number of nodes required to be deployed after the optimizer is discretized. Also, it is shown in [2] that the vector field that minimizes (5), D * (z), has the following property:…”
Section: Background: Continuous Information Flow Modelmentioning
confidence: 99%
“…Solution of this PDE leads to a simple mechanism for routing the traffic: each node forwards the traffic to a neighbor with least potential (steepest potential decent). In [4], it is shown that this routing method, minimizes the number of nodes required to carry a specified information density in a network area.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the optimal paths are obtained by solving a set of partial differential equations similar to Maxwell's equations. Using a similar analogy with electrostatics, Toumpis and Tassiulas [2] consider a related problem of optimal placement of the nodes in a dense sensor network. It is assumed that, at any point in the network, the information flows exactly in one direction.…”
Section: Related Workmentioning
confidence: 99%
“…In practice, this means that, locally, a packet is forwarded to the furthest reachable node in that direction. 1 At the macroscopic level, one is concerned with the end-to-end paths, and the assumption of a strong separation between the different scales justifies describing the underlying network as a continuous medium and the paths as smooth continuous curves [2][3][4][5][6][7][8][9][10]. In the present paper, we focus on studying the optimal paths at the macroscopic level.…”
Section: Introductionmentioning
confidence: 99%
“…This work was followed by [3,4], where the author showed that the methodology leads to an optimal deployment of sensor nodes. In this methodology a traffic density vector field models transportation of traffic in a wireless network.…”
Section: Introductionmentioning
confidence: 99%